Survival in patients with acute non-lymphoblastic leukemia at the "Dr. Gustavo Aldereguía Lima". Hospital. A ten years experience - Rafael Alejandro Gómez Baute; Julio Dámaso Fernández Águila.; Liermis Dita Salabert; Tamara Guerra Alfonso (Medisur)
Background: acute non-lymphoblastic leukemias account for 80% of leukemias in adults. Its incidence increases with age up to 20 per 100 000 in over 70 years old patients. Objective: To characterize the survival of patients with acute non-lymphoblastic leukemia at the "Dr. Gustavo Aldereguía Lima " Hospital of Cienfuegos. Methods: A case series which included all patients who underwent diagnosis of acute non-lymphoblastic leukemia between 1999 and 2010 at the Hospital of Cienfuegos. Data were obtained from the record book of hematological malignancies from the Oncohematology Department. Such variables like age, sex, morphological variant of the leukemia, incidence per year and overall survival were analyzed according to sex, morphological variant, origin, age and bone marrow transplant. Results: The average age of the studied series was 55 years old . Males were predominant with 55 cases. The most common morphological variant was the myelomonocytic. Overall survival of the series was 20% with a median follow-up of 60 months. Overall survival was slightly higher in females (25% vs 18%). The patients who underwent some form of transplant had a better survival (75% vs 13%). Conclusions: The survival of patients with acute non-lymphoblastic leukemia at the "Dr. Aldereguía Gustavo Lima" Hospital is very limited.